Optimization of Service Field of Communications, Information Technology, Coding and Statisticson The Government of District Cianjur - Nurdin, Burhan (International Journal of Educational Research & Social Sciences, 2021)
The Office of Communication, Informatics, Encryption and Statistics of Cianjur Regency is an institution engaged in the field of communication, information, coding and statistics that helps local governments in serving the people of Cianjur. Although according to the establishment of the Office of Communication, Informatics, Encryption and Statistics, it has been around for a long time, nevertheless it is still faced with problems that require resolution. If the problem is classified, it is related to the lack or weakness of services in the fields of communication, informatics and coding. This situation makes the management team plan, and formulate what actions are appropriate to overcome this problem. The theory used in this research is the theory of Plan, Do, Check, Action by W. Edwards Deming and Walter Shewhart. The research approach used is qualitative, with descriptive analytical methods.This study resulted in a discussion that the Cianjur Regency Communication, Informatics, Codification and Statistics Office carried out planning efforts in managerial terms, improving e-government service facilities and infrastructure, expanding the power and space of information communication media, increasing the intensity of dissemination and distribution of information on government administration, technical review of the general plan of the space pattern for the placement of wireless communication infrastructure within the framework of controlling the construction of telecommunications towers, and preparation of a technical study on the general plan of communication infrastructure as a reference for policies and development of communication, informatics, coding and statistics The strategy for developing communication, informatics, coding and statistics is directed at structuring the implementation of dissemination and distribution of information on governance and development through updating e-government activities, building outdoor information media, revitalizing radio broadcast transmittance, developing Cianjur Satu Data, Cianjur Regency and developing data compliance. Cianjur Regency macro indicators as well as fulfillment of coding information services.